The Effects of the Architectural Lineaments on the Stability of the Interior Design Configuration for the Historical Buildings Across Time An Analytical Study for Samples from Erbil Citadel in Kurdistan Region of Iraq - Issa, Naram M.; Khalil, Kadhim F. (Sulaimani Journal for Engineering Sciences, 2019)
The architectural conservation is one of the important practices for preservation the heritage and local identity of buildings., While architectural lineaments gives identity for each architectural style, however, Erbil Citadel preservation project had analyzed and documented without any studies before and after the preservation and rehabilitation. Theories of the interior design configuration had applied as a way to be sure from the architectural lineaments before and after the preservation and rehabilitation through study the characteristics of those spaces. The research problem is that there is no study that dealt with geometrical means that stands behind the stability of the interior design configuration for the historical buildings across time. The idea behind this research is to provide a mathematical measurement of the architectural lineaments stability before and after the preservation and rehabilitation. The research hypothesis is that the stability of the interior design configuration for the historical buildings back to the stability of the architectural lineaments before and after the preservation and rehabilitation.
Keywords: democracy; organic architecture; democratic architecture